Analisis Biaya Pemupukan Tanaman Menghasilkan Kelapa Sawit (Elaeis Guineensis Jacq.) Divisi I Kebun Langga Payung P.T. Tapian Nadenggan - Yazid, Abu (Jurnal Sosiologi Pertanian dan Agribisnis, 2021)
Fertilizer is one of the main factors that determines plant productivity. One alternative fertilizer cost efficiency measure that can be taken is to increase the effectiveness of fertilizers in the field (Poeloengan et. al., 2000). The aim of fertilization in the field can be formulated in general policy as follows, the target of fertilizer application is to achieve 100% fertilizer application in the field with the correct application method and the right time of fertilization and each plant receives the amount of fertilizer according to the dose specified in the fertilizer recommendations to ensure adequate plant nutrients. and achieving high production for Producing Crops (PC) (Fathoni et. al., 2011). This research uses a descriptive analysis method regarding the costs of fertilization on high-yielding oil palm plants in Division I of Langga Payung Plantation P.T. Tapian Nadenggan. Observation indicators are data on recommendations for oil palm plant fertilization (type and dose of fertilizer in 2016-2018); Fertilization realization data for 2016-2018; Fertilization recommendations and fertilizer realization are made for a period of one year. Recommendation and realization data were analyzed using Student's t-Test at α = 5% to compare data per year. Cost of fertilizing plants producing oil palm (Elaeis guineensis Jacq.) Division I Langga Payung Plantation P.T. Tapian Nadenggan is influenced by 3 components, namely: Purchase of fertilizer, transportation and wages of sowers, which is based on research data that the components of fertilizer costs in 2018 are not significantly different from the components of fertilizer costs in 2017 and 2016. Likewise, the fertilization cost component in 2017 is not significantly different from the fertilization cost component in 2016.